(Method for HPLC Analysis of Active Compounds in Ginger (Zingiber officinale) - Maria Novelina.S, Yus; Maman Rohaman, M; Wijaya, Hendra (Balai Besar Industri Agro, 2011)
The studies Ginger (zingiber officinale) is one of herb plant which contains various of active compounds,which is proved has function hasÂ to human health .in indonesia , there are 3 main ginger variaties,those are :giant gingger (zingiber officinale var .officinale),emprit ginger (Zingiber officinale var. amarum ), and red ginger (Zingiber officinale var.rubrum) .Each ofthem has different characteristic and function .the problems which often occurs are ginger counterfeting,often mixed with other gingers.this counterfeiting difficult to be detected with conventional test method. therefore needed study about characteristic of each ginger with HPLC so counterfeiting able to be traced .Asensitive and accurate high-performance liquid chromatography (HPLC) method has been developed to determine the quantity of active componen in the methanolic extract of Zingiber officinale Bioactive component was separated on persuit C18 Column (250 mm x4.6 mm,particle size:5 um)with gradient system of water and acetonitrile as mobile phase. the calibration plot was linear in the range of 0.10-150 mg/L .of 6-,8-,10-gingerol and the correlation coefficient of o.9998 was indicative of good linear dependence of peak area on concentration .the limit of detection (LOD) OF 6-gingerol ,8-ginggerol ,6-shogaol andÂ 6-shogaol and the correlation coefficient were 2,34 1,06; 1,25, and 0,67 mg/l and limit of detection (LOD)were 7,81 :3,53 :3,53; 4,18 and 2,29 mg/lrespectively.the developed HPLC method was found selective,precise and accurate,and can be used for routine analysis of gingers in the quality control laboratories .